The fungicide imazalil induces developmental abnormalities and alters locomotor activity during early developmental stages in zebrafish. (June 2016) - Jin, Yuanxiang; Zhu, Zhihong; Wang, Yueyi; Yang, Enlu; Feng, Xiayan; Fu, Zhengwei
Abstract: The fungicide imazalil (IMZ) is used extensively to protect vegetable fields, fruit plantations and post-harvest crops from rot. Likely due to its wide-spread use, IMZ is frequently detected in vegetable, fruit, soil and even surface water samples. Even though several previous studies have reported on the neurotoxicity of IMZ, its effects on the neurobehavior of zebrafish have received little attention to date. In this study, we show that the heartbeat and hatchability of zebrafish were significantly influenced by IMZ concentrations of 300 μg L −1 or higher. Moreover, in zebrafish larvae, locomotor behaviors such as average swimming speed and swimming distance were significantly decreased after exposure to 300 μg L −1 IMZ for 96 h, and acetylcholinesterase (AChE) expression and activity were consistently inhibited in IMZ-treated fish. Our results further suggest that IMZ could act as a neuroendocrine disruptor by decreasing the expression of neurotoxicity-related genes such as Glial fibrillary acidic protein (Gfap), Myelin basic protein (Mbp) and Sonic hedgehog a (Shha) during early developmental stages of zebrafish. In conclusion, we show that exposure to IMZ has the potential to induce developmental toxicity and locomotor behavior abnormalities during zebrafish development. Highlights: Effect of IMZ on neurobehavioral toxicity in larval zebrafish is evaluated. The swimming behaviors of larval zebrafish are disturbed by IMZ. IMZ reduces the activity of AChE and dopamine contents in larval zebrafish. IMZ alters the transcriptional levels of some genes related to neurotoxicity.